The Relationship Between Leadership, Span of Control, Perception of Islamic Products and Services, Perception of Internal Service Quality and the Agents' Job Satisfaction: A Case of Unit Trust Agents in Johor Bahru - Kwan, Chin Swee; Isa, Filzah Md (International Review of Management and Marketing, 2016)
One major issue facing the unit trust industry in Malaysia is the job satisfaction of unit agents. Past studies have shown that job satisfaction could be influenced by a variety of factors. Therefore, this study determines to investigate the relationship between leadership, span of control, perception of Islamic unit trust products and services, perception of internal service quality and job satisfaction. The sample consisted of 303 respondents of unit trust agents. A total of four hypotheses was developed, and all were supported. The results showed all of these factors had a significant relationship with job satisfaction. These findings clearly imply that good leadership, low span of control, positive perception of Islamic unit trust products and services, and high internal service quality can lead to higher job satisfaction among the agents. Thus, they should assist policy makers, practitioners and marketers in their sustainability and growth efforts. Keywords: leadership, span of control, job satisfaction JEL Classifications: D23, J28